Lack of consensus in the choice of termination of pregnancy for Turner syndrome in France - Monika Hermann; Babak Khoshnood; Olivia Anselem; Claire Bouvattier; Aurélie Coussement; Sophie Brisset; Alexandra Benachi; Vassilis Tsatsaris (BMC, 2019)
Abstract Background The observed rate of termination of pregnancy (TOP) for Turner syndrome varies worldwide and even within countries. In this vignette study we quantified agreement among ten multidisciplinary prenatal diagnosis centers in Paris. Methods We submitted online three cases of Turner syndrome (increased nuchal translucency, normal ultrasound, aortic coarctation) to fetal medicine experts: one obstetrician, one pediatrician and one geneticist in each of the ten Parisian centers. Each case was presented in the form of a progressive clinical history with conditional links dependent upon responses. The background to each case was provided, along with the medical history of the parents and the counseling they got from medical staff. The experts indicated online whether or not they would accept the parents' request for TOP. We assessed the percentage of agreement for acceptance or refusal of TOP. We also used a multilevel logistic regression model to evaluate differences among obstetrician-gynecologists, pediatricians and cytogeneticists. Results Overall agreement among the experts to accept or refuse TOP was, respectively, 25 and 28%. The percentage of disagreement was 47%. The percentage of agreement to accept TOP was 33, 8 and 33% for obstetrician-gynecologists, pediatricians and cytogeneticists, respectively. The respective percentages of agreement to refuse TOP were 19, 47 and 26%. Conclusion Our results show the lack of consensus with regard to decisions related to termination of pregnancy for Turner Syndrome. This lack of consensus in turn underscores the importance of multidisciplinary management of these pregnancies in specialized fetal medicine centers.